Analyzing the defense response mechanism of Atractylodes macrocephala to Fusarium oxysporum through small RNA and degradome sequencing - Fan, Sen; Tang, Yunjia; Zhu, Na; Meng, Qingling; Zhou, Yanguang; Zhao, Yujin; Xu, Jingyan; Gu, Chenxian; Dai, Shijie; Zhu, Bo; Yuan, Xiaofeng (Frontiers in Plant Science, 2024)
Fusarium oxysporum is a significant soil-borne fungal pathogen that affects over 100 plant species, including crucial crops like tomatoes, bananas, cotton, cucumbers, and watermelons, leading to wilting, yellowing, growth inhibition, and ultimately plant death. The root rot disease of A. macrocephala, caused by F. oxysporum, is one of the most serious diseases in continuous cropping, which seriously affects its sustainable development. In this study, we explored the interaction between A. macrocephala and F. oxysporum through integrated small RNA (sRNA) and degradome sequencing to uncover the microRNA (miRNA)-mediated defense mechanisms. We identified colonization of F. oxysporum in A. macrocephala roots on day 6. Nine sRNA samples were sequenced to examine the dynamic changes in miRNA expression in A. macrocephala infected by F. oxysporum at 0, 6, and 12 days after inoculation. Furthermore, we using degradome sequencing and quantitative real-time PCR (qRT-PCR), validated four miRNA/target regulatory units involved in A. macrocephala-F. oxysporum interactions. This study provides new insights into the molecular mechanisms underlying A. macrocephala's early defense against F. oxysporum infection, suggesting directions for enhancing resistance against this pathogen.